Disparities in prostate cancer screening practices among general practitioners and urologists (PROSHADE study): A cross-sectional study - Blanca Lumbreras; Lucy A. Parker; Pablo Alonso-Coello; Juan-Pablo Caballero-Romeu; Ignacio Párraga-Martínez; Luis Prieto; Irene Moral-Peláez; Mª del Campo-Giménez; Luis Gómez-Pérez; Ana Cebrián; Maite López-Garrigós; Elena Ronda; et al. (PLoS ONE, 2026)
Introduction Recent European recommendations promote risk-based, patient-centred screening models that emphasise shared decision-making (SDM) in prostate cancer (PCa) screening with prostate-specific antigen (PSA) testing. Understanding how clinicians apply these practices is essential, particularly given the roles of general practitioners (GPs) and urologists in detection. The aim of this study was to compare the knowledge, attitudes, and practices of GPs and urologists in Spain regarding PSA testing, PCa screening, and SDM implementation. Methods Cross-sectional survey conducted via an online questionnaire. Members of the Spanish Association of Urology (AEU) and the Spanish Society of Family and Community Medicine (semFYC) were surveyed online. The survey, developed and validated using a modified Delphi process, contained 18 items assessing clinicians’ opinions, practices, and knowledge of guidelines. Data from 494 respondents (280 GPs and 214 urologists) were analysed using descriptive statistics and logistic regression to explore differences between specialty, demographics, and screening practices. Results Urologists were more likely than GPs to consider PSA testing important (97.2% vs. 83.2%) and useful (96% vs. 44.4%), and to recommend it to relatives (90.4% vs. 44%) (all p < 0.001). They reported to initiate testing earlier (50–59 years: 77.8% vs. 32%) and reported to perform it more frequently (annual testing: 60.7% vs. 45.6%, p < 0.001). GPs reported to more often engaged in SDM when ordering PSA tests (69.7% vs. 10%, p < 0.001). Knowledge of guidelines was higher among urologists (91% vs. 24.1%), yet 75.4% stated that they had not modified practice following updated recommendations. Conclusions Significant specialty-based differences exist in PSA testing practices, perceptions, and guideline adherence. Urologists show greater familiarity with recommendations, while GPs reported more patient-centred communication.